The mindful Christian : cultivating a life of intentionality, openness, and faith - Kraegel, Irene (Fortress Press, 2020)
"The Mindful Christian provides readers with an overview of mindfulness practice through the lens of faith, showing how the ancient healing practice of mindfulness can help them live more joyfully and wholeheartedly. For Christians who are experiencing emotional pain, spiritual lethargy, or feelings of disconnection--or for Christians who are simply curious about how mindfulness can fit with their lives and their faith--this book will help them learn about and engage mindfulness practices in ways that leave them more compassionate, joyful, content, and at peace with themselves--and with God. The book offers easy-to-do mindfulness practices that will impact daily activities and relationships--empowering readers with the benefits of mindfulness for their emotional, spiritual, and relational health within the Christian life."